Comparative transcriptomics of two Valsa pyri isolates uncover different strategies for virulence and growth. (October 2018) - He, Feng; Zhang, Xiong; Li, Binxin; Safdar, Asma; Ai, Gan; Kange, Alex Machio; Zhao, Yancun; Cao, Haiqun; Dou, Daolong; Liu, Fengquan
Abstract: Valsa pyri, an ascomycete pathogen that is a member of the Valsaceae family (Sordariomycetes, Diaporthales), which causes pear or apple canker and leads to tree death and massive yield losses. Here, we selected two V. pyri isolates (Vp14 and Vp297) that exhibited different invasion abilities for transcriptomics analyses. Compared toVp297, Vp14 had stronger virulence and spread faster on host-like nutrients. Four samples, including mycelium or infectious mycelium, of the two isolates were sequenced. Clean reads were mapped to the V. pyri genome, and 12490 transcripts and 178 new genes were identified. There were dramatically fewer differentially expressed genes (DEGs) in Vp14 than in Vp297. According to GO and COG annotations, there were both more up- and down-regulated genes in Vp297 than in Vp14 except for genes involved in amino acid transport and metabolism, carbohydrate transport and metabolism, peroxidases and so on. Specific up-regulated DEGs, including genes encoding cell wall degrading enzymes and genes involved in nitrogen metabolism and peroxidases which play crucial roles in virulence and infectious growth, were especially enriched inVp14. These results indicate that the Vp14 isolate may infect its host and take up nutrition more efficiently, reflecting a stronger ability for invasion or infectious growth. Our analysesindicate that a successful V. pyri infection involves multiple instances of transcriptome remodeling to regulate gene functions. Comparative transcriptomics between isolates of V. pyri may aid in our understanding of the virulence mechanism of this pathogen. Highlights: The two Valsa pyri isolates differ in their utilization of mineral or host nutrition in vitro. Greater specific genes were upregulated in the stronger virulence isolate Vp14, involve in cell wall degrading enzymes, peroxidases and nitrogen metabolism, which are required for virulence and necrotrophic growth of fungi.. This is the first comparative transcriptomics research uncovering the difference between Valsa pyri isolates.